Implementing a Triple L-shape Resonator on a Monopole Antenna for Multiband Operation in WLAN, WiMAX, 4G LTE, and 5G Sub-6G Networks - Chudpooti, Nonchanutt; Chanwattanapong, Wanchalerm; Jangjing, Thinnawat; Rakluea, Paitoon; Wongsin, Norakamon; Suangun, Thanakarn; Mahatthanajatuphat, Chatree; Akkaraekthalin, Prayoot; Chutchavong, Vanvisa (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2025)
The present research proposes an innovative multiband antenna design including a triple L-shape structure. This design is specifically targeted for utilization in a wireless local area network (WLAN), worldwide interoperability for microwave access (WiMAX), 4G LTE, and 5G Sub-6G networks. The antenna being considered is designed in an L-shaped layout, consisting of three separate components. The triple L-shape demonstrates the capacity to independently produce resonant frequencies. The middle L-shape, which is the longest, is notably responsible for generating the initial resonance frequency at 1.8 GHz. In addition, the L-shaped structure on the right exhibits a secondary resonance frequency of 2.45 GHz, whilst the L-shaped structure on the left generates a tertiary resonance frequency of 3.6 GHz. The proposed antenna demonstrates an extra resonance frequency of 4.6 GHz, which fits within the application frequency range of 5.2 GHz. The presence of the L-shape structure in the middle and right side of the suggested antenna arrangement is responsible for generating the 4th resonance frequency, which can be attributed to the harmonic frequency. The antenna being discussed is fabricated on a FR4 substrate, measuring 30×50 mm2 in size. After performing testing on the antenna, it is evident that both the simulation and measurement results demonstrate a suitable response across the whole operational frequency range. The antenna is capable of operating efficiently at specific frequencies. These frequencies include 1.8 GHz (1.71 GHz - 1.89 GHz) for LTE 1800, 2.45 GHz (2.39 GHz - 2.71 GHz) for IEEE 802.11b&g WLAN systems, LTE 2600, and 5G Sub-6G network, and 3.6 GHz (3.2 GHz - 5.37 GHz) for 5G Sub-6G network, WiMAX system, and IEEE 802.11a WLAN system. The success of this performance is demonstrated by the magnitude of the reflection coefficient, represented as |S11|, which consistently stays below -10 dB. The antenna’s average gain across all operational frequencies is approximately 2.5 dBi. Moreover, the antenna’s radiation pattern maintains a consistent omnidirectional characteristic over the frequency bands of 1.8 GHz, 2.45 GHz, and 3.6 GHz. However, the radiation pattern at a frequency of 5.2 GHz displays distortion due to the antenna’s higher-order mode. Furthermore, the antenna maintains its efficacy in wireless communication systems, such as devices that combine Wi-Fi and mobile cellular 4G&5G technologies in a single unit, occasionally called pocket Wi-Fi + 4G&5G cellular.